High-temperature performance of ferritic steels in fireside corrosion regimes: temperature and deposits - Dudziak, T.; Hussain, Tanvir; Simms, N.J. (Springer, 2016)
The paper reports high temperature resistance of ferritic steels in fireside corrosion regime in terms of temperature and deposits aggressiveness. Four candidate power plant steels: 15Mo3, T22, T23 and T91 were exposed under simulated air-fired combustion environment for 1000 h. The tests were conducted at 600, 650 and 700 °C according to deposit-recoat test method. Post-exposed samples were examined via dimensional metrology (the main route to quantify metal loss), and mass change data were recorded to perform the study of kinetic behavior at elevated temperatures. Microstructural investigations using ESEM-EDX were performed in order to investigate corrosion degradation and thickness of the scales. The ranking of the steels from most to the least damage was 15Mo3 > T22 > T23 > T91 in all three temperatures. The highest rate of corrosion in all temperatures occurred under the screening deposit.